Congenital symmetrical circumscribed patterned non-scarring alopecia of eyebrows: a variant of congenital triangular alopecia or an anatomical variation?. Issue 5 (24th May 2019) - Yadav, Deepika; Khandpur, Sujay; Subhadarshani, Sweta; Sahni, Kanika
Abstract : Triangular alopecia presents as a unilateral triangular-shaped non-scarring alopecia usually involving the temporal scalp. There are few reports of occipital scalp involvement and bilateral disease. Usually it is seen at 2–3 years of age but occasionally can be present at birth. Here we present a unique case of triangular alopecia involving the eyebrows in a 23-year-old man. He had bilateral symmetrical involvement since birth. Points in favour of triangular alopecia in our case were non-scarring alopecia, oval-to-triangular shape, fringe of terminal hair at superior margin; trichoscopy showing significant decrease in hair diameter diversity with increased number of vellus and intermediate hair and histopathology showing normal hair follicle density and increased vellus and intermediate hair (miniaturisation) with absence of inflammation on histopathology. Other differential diagnoses kept were partial duplication of eyebrows, congenital alopecia areata and mild form of ectodermal dysplasia.